Financial Feasibility Analysis of Manufacturing Body Scrub from Coffee Waste - Adrinoviarini, Adrinoviarini; Nanda, Ririn Fatma; Robbani, Syifa'; Abdillah, Taufik (Jurnal Agrinika: Jurnal Agroteknologi dan Agribisnis, 2024)
Coffee grounds, a residual product stemming from the processing of coffee beverages, manifest as a compelling resource for economic exploitation in the manufacturing realm, particularly in the creation of diverse processed commodities such as body scrubs. The utilization of coffee grounds as the principal ingredient for body scrub fabrication epitomizes a proactive strategy aimed at ameliorating the surplus waste generated during coffee processing endeavors. Consequently, undertaking a meticulous financial evaluation of the coffee grounds scrub manufacturing enterprise emerges as an indispensable step towards facilitating business expansion. This comprehensive study meticulously examines the financial viability associated with establishing a specialized venture dedicated to the production of body scrub derived from coffee waste. Employing a multifaceted approach, the investigation harnesses both primary and secondary data sources in conjunction with sophisticated quantitative analysis techniques. The research methodology incorporates a series of empirical experiments conducted within the production framework, utilizing coffee grounds procured from the esteemed Laiyo Coffee Roaster. Through rigorous financial computations, the analysis unveils a favorable Net Present Value amounting to IDR184,709,323, coupled with an impressive internal rate of return standing at 45%. Furthermore, the assessment delineates a succinct payback period of 1.6 years, alongside a commendable benefit-cost ratio of 1.7, contingent upon the realization of predefined assumptions. The adherence to these stringent investment benchmarks unequivocally underscores the practical feasibility of embarking upon coffee grounds scrub production endeavors, provided the project attains anticipated revenue milestones, encompassing IDR491,666,667. Additionally, the venture anticipates post-tax profits totaling IDR195,607,667, correlating with a substantial profit margin of 39.78%.